Reducing SMEs informal economy through institutionalization: the MNC-academia-SMEs business model (Disminuyendo la economía informal de las PyMEs por medio de la institucionalización: Modelo empresa multinacionalacademia-PyMEs) - Lira Arjona, Alfonso López; Cobas Flores, Elisa; Calderón Valencia, Cecilia (Facultad de Contaduría Pública y Administración U.A.N.L., 2014)
Abstract. The informal sector has been growing throughout the last century in emerging economies. Particularly in Latin America, both a long-term instability in economic and political environments, and a continuous migration from rural to urban areas; have triggered the appearance of unregulated businesses and employments. Small and Medium-sized Enterprises (SMEs) operate informally in one or more business processes, in order to reduce costs and maximize profits. Leaving aside tax evasion and illegal labor, such SMEs often have low technology and an unskilled work force; which threatens its survival in highly competitive environments. The purpose of this paper is to highlight the impact of the Multi National Corporation (MNC) and the Academia in the formalization of SMEs. This is aimed through a collaborative model for the institutionalization of operational and managerial knowledge within SMEs. Qualitative results indicate that improvements are triggered by a self-conscious awareness of the value derived from institutionalizing best business practices.